Synthesis of themes and policy issues - Alston, Julian M.; Pardey, Philip G.; Piggott, Roley R. (International Food Policy Research Institute, 2006)
The developing world is not likely to benefit from rich-country agricultural research in the future as much as it has in the past, and so it will need to become more self-reliant in the provision of agricultural R&D. But even the richest countries continue to underinvest in certain types of agricultural R&D (Alston, Pardey, and Smith 1999). To add to the complexity of policymaking, changes are taking place in the technical and economic basis for agricultural R&D per se, as well as in the structure of the economy, such as decreasing trade barriers and changing consumer and producer demands. These problems of underinvestment and policy challenges are more acute in developing countries than in developed countries; and the task of correcting for the underinvestment in agricultural R&D is therefore even greater. But much has to be learned about what is wrong currently, and why, before effective remedies can be designed and put in place.